Intermolecular interactions of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (P(HB-co-HV)) with PHB-type crystal structure and PHV-type crystal structure studied by low-frequency Raman and terahertz spectroscopy. (17th January 2018) - Marlina, Dian; Sato, Harumi; Hoshina, Hiromichi; Ozaki, Yukihiro
Abstract: Composition-, temperature-, and polarization-dependent low-frequency Raman and terahertz (far-infrared; FIR) spectra were measured for poly(3-hydroxybutyrate- co -3-hydroxyvalerate) (P(HB- co -HV)) with PHB-type crystal structure and PHV-type crystal structure to investigate their intermolecular interactions. Band assignments were attempted by comparing the low-frequency Raman and terahertz (FIR) spectra of P(HB- co -HV) with the varying HV content with the corresponding spectra of PHB and by observing spectral variations. The spectra of P(HB- co -HV) (HV = 9, 15, and 21 mol%) are similar to the corresponding spectra of PHB. There are two bands at 97 and 82 cm −1 which are assigned to a spring type vibrational mode of the helical structure and to the mode reflecting the intermolecular interaction (CH3 ⋯O=C hydrogen bond), respectively. The low-frequency Raman and terahertz spectra of P(HB- co -HV) with HV content of 66 and 88.6 mol% show bands at 91 and 78 cm −1 . The 78 cm −1 band is assigned to the intermolecular interaction (CH2 ⋯O=C hydrogen bond). In contrast to the 97 cm −1 band of P(HB- co -HV) with the low HV content, the 91 cm −1 band of P(HB- co -HV) with the high HV content show a temperature-dependent shift by 4 cm −1 . Thus, although it seems that both 97 and 91 cm −1 bands are due to spring-like vibrational modes, the nature of two vibrational modes seems to be significantly different, reflecting the difference in the intermolecular interaction. Graphical abstract: Highlights: Two types of hydrogen bonding in P(HB- co -HV) were investigated by using low-frequency Raman and terahertz spectroscopy. The peak assignment of P(HB- co -HV) in low-frequency region were made by temperature- and polarization-dependent spectroscopy. Low-frequency vibrational spectra reflect more directly the intermolecular interaction than high-frequency vibrational spectra.